Criteria for Ethical Allocation of Scarce Healthcare Resources: Rationing vs. Rationalizing in the Treatment for the Elderly - Maria do Céu Patrão Neves (Philosophies, 2022)
This paper stems from the current global worsening of the scarcity of resources for healthcare, which will deepen even more in future public emergencies. This justifies strengthening the reflection on the allocation of resources which, in addition to considering technical issues, should also involve ethical concerns. The two plans in which the allocation of resources develops—macro and micro—are then systematized, both requiring the identification of ethical criteria for the respective complex decision-making. Then, we describe how the complexity at the macro level focuses on the joint consideration of the rectitude of the principles, the goodness of the ends, and the integrity—respectively the deontological, teleological, and procedural perspectives; and at the micro level, it focuses in prioritizing people, which can result in the exclusion of some, as happened with the elderly during peaks of COVID-19. The main objective of this article is to show that, in public health emergency situations, in which the daily criteria for prioritizing access to health care are not efficient, it is possible not only to ration the available means but also to rationalize them. We argue that rationing and rationalization are different concepts, entail different consequences, have different ethical foundations, and draw different guidelines for patient care. We apply them to the distribution of intensive care and vaccines to the elderly thus demonstrating the ethically legitimate domain of implementation of each of these two prioritization criteria. We conclude that rationalization respects more strictly the core ethical principles of our common morality.